Traditional dance learning as an effort to introduce Sundanese culture in PAUD Riyadussholihin - R Dara Sakhila; Muhammad Rafli Fauji; Yuliawan Kasmahidayat (Universitas Pendidikan Indonesia, 2025)
Dance education in early childhood serves as a medium for shaping positive character during children's developmental stages. At this age, children also undergo cultural transitions, including exposure to Sundanese culture, which carries values, knowledge, and beliefs. This community service aims to introduce traditional dance as a method to promote Sundanese culture among early childhood students. The service was carried out at PAUD Riyadussholihin in Cipongporang, Katapang, with 35 participants aged 4-6 years. The goal was to foster an appreciation for local culture and instill a sense of national pride through dance. The method used in this service is hands-on practice. Students were introduced to traditional Sundanese dances, such as